A Study on Factors Related to Market Capitalization in Indian Manufacturing Firms - Jagannathan, Uday Kumar; Khan, Nawaz (Indian Journal of Finance, 2019)
Manufacturing firms have always been a significant contributor to the Indian GDP and has been a fast-developing sector. The scope of the study included all publicly listed manufacturing firms in India for the time period between 2009–2018. Suitable pooled OLS regressions were run for each hypothesis. In all regressions, the dependent variable was the percent change in market capitalization for each firm for each year. In the group classification of risk and profitability, the variables regressed were the levered beta, return on assets, return on equity, debt to equity ratio, and a dummy variable indicating the financial crisis. For the group of variables under compensation to investors, variables selected were earnings per share, dividend paid per share, and interest paid divided by total assets. For the asset efficiency group, the variables selected included total assets, current assets, asset turnover ratio, cash turnover ratio, and cash flow to sales ratio. Finally, for the investment policy decision group, firms were segregated on the basis of being conservative to aggressive on the basis of investments in assets and the difference in the investment level between conservative and aggressive firms (CMA) were regressed against the dependent variable. The study found that variables - Leveraged beta was 5% significant; ROA, ROE, DUMMY 1, EPS, and debt to equity were 1% significant; DPS was 5% significant; while EPS and debt to equity were 1% significant. Further, for asset efficiency, the asset turnover and the cash turnover ratios were 5% significant, and finally, investment policy as proxied by CMA was 1% significant.